ANALISIS YURIDIS TERHADAP EKSEKUSI HAK TANGGUNGAN (STUDI KASUS PUTUSAN PERKARA PERDATA NOMOR 38/PDT.G/2012/PN.PBR) - Simamora, Try Jaya; Bachtiar, Maryati; Fitriani, Riska (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Land as collateral is a good guarantee property because it has economic value, therefore the author is interested in the title "Juridical Analysis Against Execution of Mortality Rights (Case Study Case PerdataNo.38 / PDT.G / 2012 / PN.PBR)." Based on the results of the discussion can be concluded the existence of the concept of civil lawsuit case is due to an agreement between the debtor and the creditor who experienced wanprestasi.The creditor takes the action of execution, but if judged by the amount of collateral, it should not be able to immediately auction the land under suspension, without the knowledge of the landowner, resulting in a prolonged conflict until the end of 2012 with the Court'sEnsure the repayment of the landowner's debts with the license of two land plots of Certificate of Property, will the landowner's business fail, the credit to the Bank as the creditor, the congestion. Finally, the Bank has passed the execution of mortgages (mortgages) through the District Court Pekanbaru with the determination of the amount of compensation amounting to Rp.104.009.759, -then then unilaterally changed to Rp.420.780.749.779.The owner of the land as the debtor has been impaired, hence the barrage of problems and cases related to the execution of the above mortgages, illustrated some efforts made by the parties until the verdict of civil cases No.38 / Pdt.G / 2012 / PN.PBR (with the permissibility of the indebted, either moving or immovable, whether existing or new, will be in the future, become a liability for all personal engagements. "